2012
DOI: 10.1093/cid/cis786
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Ribotype Does Not Predict Severe Infection

Abstract: Ribotype is not a significant predictor of severe CDI when adjusted for the influence of any other variables separately or in combination. White blood cell count and albumin level are the most clinically relevant predictors of severe CDI cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
165
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(179 citation statements)
references
References 41 publications
11
165
2
1
Order By: Relevance
“…The finding also suggests that C. difficile ribotypes may not be determinants of the development of symptomatic infection but, rather, that the development of symptoms may be mainly driven by host factors, such as immune state and disruption of the gut microbiome by exposure to antimicrobials or underlying conditions affecting the gastrointestinal tract (17)(18)(19). Our findings differ from those of a previous study in which a binary toxin-producing C. difficile strain (i.e., ribotype 027) was more likely than other strains to cause symptomatic disease (6).…”
Section: Discussionmentioning
confidence: 99%
“…The finding also suggests that C. difficile ribotypes may not be determinants of the development of symptomatic infection but, rather, that the development of symptoms may be mainly driven by host factors, such as immune state and disruption of the gut microbiome by exposure to antimicrobials or underlying conditions affecting the gastrointestinal tract (17)(18)(19). Our findings differ from those of a previous study in which a binary toxin-producing C. difficile strain (i.e., ribotype 027) was more likely than other strains to cause symptomatic disease (6).…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have demonstrated more severe disease and increased mortality associated with ribotype 027 (16,19), more recent studies have challenged this observation (21,22). In the latter studies, when other covariates were considered, the ribotype of the infecting organism was not found to be a significant predictor of severe CDI (21). Currently, there are no recommendations to alter infection control practices based upon ribotype.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that this may not always be the case. A recent study by Walk and colleagues found that while the NAP1/BI/027 strain is associated with severe disease, it is not the sole predictor of disease severity (173). Other factors, such as white blood cell count, may be better clinical indicators of the severity of disease.…”
Section: History and Emergence Of Nap1/027/bi Strainsmentioning
confidence: 99%